Septicemia in an Indian Rhesus Macaque (Macaca mulatta) associated with Providencia stuartii. Issue 6 (28th July 2016) - Liu, David X.; Didier, Peter J.; Plauche, Gail; Pahar, Bapi
Abstract: Providencia stuartii ( P .  stuartii ) is an opportunistic pathogen and major concern in urinary catheter‐related infections in human medicine. Here we report P. stuartii ‐induced septicemia in an eighteen‐year‐old, female India‐origin Rhesus macaque with multiple traumatic wounds. The animal had neutrophilic leukocytosis, necrosuppurative meningoencephalitis, hypophysitis and bronchopneumonia with vasculitis, thrombosis, and clusters of extracellular Gram‐negative bacilli. P. stuartii was isolated from the lesions of the brain and lung and confirmed by PCR and sequencing. To the authors' knowledge, this is the first case of septicemia associated with P. stuartii in a non‐human primate.